Kepatuhan Minum Obat Pada Pasien Tuberkulosis Paru di Ruang Isolasi RSUD Muara Teweh Tahun 2023 - Armintoyono, Armintoyono; Unja, Ermeisi Er; Warjiman, Warjiman; Rachman, Aulia (LPPM Universitas Sari Mulia, 2023)
Background : TB treatment problem factor is treatment adherence. Failure to complete treatment can cause patients to relapse, potentially infect contacts and increase the risk of drug resistance, so adherence to taking medication affects the success of treatment. Objective : To purpose of this research was to how the description of drug compliance in tuberculosis patients in the isolation room of Muara Teweh Hospital in 2023. Method : This type of quantitative research. Sampling was done by total sampling technique. The total population was 36 respondents and the samples obtained were 36 respondents. The research instrument used the MMAS-8 questionnaire. Patient compliance data were classified into 3 categories, namely high, medium and low adherence. Data was analyzed descriptively and presented into tables and narrations. Result : The result showed that description of drug compliance in tuberculosis patients in the isolation room of Muara Teweh Hospital had a high category of 88,89% , a medium category of 0% and a low category of 11,11% Conclusion : Description of drug compliance in tuberculosis patients in the isolation room of Muara Teweh Hospital had a high category.